A Correlational Study of Student Factors and Performance in CPA Board Examination: a case in JRMSU - Maghinay, Leonila C. (Future Science / FSH-PH Publications, 2024)
This paper proposes to identify the necessary interventions to enhance graduates’ performance in the Certified Public Accountant Licensure Examination. It aimed to examine the relationship between identified student factors and the inconsistency in graduates' performance in the CPA board exams from 2016 to 2019. The study is based on Walberg's theory of academic achievement, which asserts that the psychological characteristics of students and their immediate environments affect educational outcomes. A descriptive research design was utilized, surveying 28 Bachelor of Science in Accountancy graduates who took the CPA board exam using a standardized checklist. Qualitative data, serving as secondary data, were analyzed through documentary analysis. Additionally, in-depth structured interviews were conducted to support the quantitative data. Results indicated that among student-related factors, only study habits significantly impacted graduates' performance in the CPA board exam. Other factors, such as academic performance, aspiration, and attitude towards accounting, were found to be insignificant. The study advocates for time management, comprehensive self-management, development of analytical skills, and maintaining a consistent desire to pass the CPA board exam and become an accountant. Future research is also recommended.